Sensorimotor Learning during a Marksmanship Task in Immersive Virtual Reality - Rao, Hrishikesh M.; Khanna, Rajan; Zielinski, David J.; Lu, Yvonne; Clements, Jillian M.; Potter, Nicholas D.; Sommer, Marc A.; Kopper, Regis; Appelbaum, Lawrence G. (Frontiers in Psychology, 2018)
Sensorimotor learning refers to improvements that occur through practice in the performance of sensory-guided motor behaviors. Leveraging novel technical capabilities of an immersive virtual environment, we probed the component kinematic processes that mediate sensorimotor learning. Twenty naïve subjects performed a simulated marksmanship task modeled after Olympic Trap Shooting standards. We measured movement kinematics and shooting performance as participants practiced 350 trials while receiving trial-by-trial feedback about shooting success. Spatiotemporal analysis of motion tracking elucidated the ballistic and refinement phases of hand movements. We found systematic changes in movement kinematics that accompanied improvements in shot accuracy during training, though reaction and response times did not change over blocks. In particular, we observed longer, slower, and more precise ballistic movements that replaced effort spent on corrections and refinement. Collectively, these results leverage developments in immersive virtual reality technology to quantify and compare the kinematics of movement during early learning of full-body sensorimotor orienting.